The changing global perspectives of successful ageing from 2019 to 2023 - Hassan, Mohammad Mujaheed; Rajeswaran, Yeshulavani; Ashari, Asmidawati; Mohd Khir, Azlina (Fakulti Ekologi Manusia, Universiti Putra Malaysia, 2024)
This review paper explores the evolving perspectives on successful ageing from 2019 to 2023. It emphasizes the increasing global significance of this concept due to the growing older population. Successful ageing is typically defined by the absence of major illnesses or disabilities, as well as the maintenance of strong cognitive and physical abilities, and active social engagement. Despite extensive research in developed countries, there is still a gap in understanding how older adults perceive successful aging. The study highlights themes such as physical & psychological well-being, social & environmental factors, financial security & independence, cultural & regional variations, and psychosocial factors. It also brings attention to the concept of gerotranscendence, which involves a positive redefinition of self and relationships, as a potential precursor to successful ageing. The review emphasizes the complexities of defining and measuring successful ageing, given the numerous definitions found in the literature, and stresses the need for a nuanced understanding to inform policies and interventions. With ageing populations on the rise, the demand for health and social care to address age-related challenges will increase. Understanding the predictors of successful ageing and the combined impacts of behaviors and biomarkers is vital for policy development. The study calls for further research into the underlying mechanisms of successful ageing and comprehensive strategies to support the ageing population globally, addressing significant challenges in areas such as pensions, housing, and social security.